Corrugated plane wave scattering by a sphere. (July 2020) - Chrissoulidis, Dimitrios; Richalot, Elodie; Lamprianidis, Aristeidis
Highlights: A pair-of-waves (pow) approach to scattering of a corrugated plane wave (cpw) by a sphere is formulated. The pow theory and code are applied to a sinusoidal wave-front incident on a sphere and to Gaussian-beam scattering by an off-axis sphere. A numerical example demonstrates that particle sizing is possible by adapting a sinusoidal wave-front to the scattering sphere. Abstract: Scattering of a corrugated plane wave (cpw) by a sphere is formulated by a pair-of-waves (pow) approach, whereby the incident wavefront is considered as a continuum of sinusoidal wavefronts and any such constituent is considered as a pair of equal-amplitude, plane, electromagnetic (em) waves which may be in- or out-of-phase and may assume either of two orthogonal polarisations. All sinusoidal constituents are propagated in the direction of the normal to the incident wavefront. We determine the constituent spectra of a cpw by use of the Fourier transform and ultimately the Lorenz-Mie coefficients that apply to cpw scattering by a sphere. We apply our approach to pow scattering by a sphere and Gaussian-beam scattering by an off-axis sphere. We present numerical results for a μ m-sized, spherical, glycerol droplet which is coupled to an incident, infrared cpw and we show how to tune an incident pow to that droplet in order to enhance backscattering. Our theory and Fortran code are validated by comparison with a commercially available FEM software.